Islamic Hotel Indicators: A Bibliometric Study - Rusydiana, Aam Slamet (The international journal of religious tourism and pilgrimage, 2021)
This study reviews research on the theme of Islamic-based hotels in reputable journals. It uses bibliometric analysis of a selected 67 articles related to Islamic hotels published by national and international journals. The entire sample of journal publications have been published in the ten years from 2011 to 2020. The results show that in researching Islamic hotels, case studies are dominated by Malaysia, following by Indonesia. Network visualisation shows that the development of Islamic hotel research is divided into 4 clusters. Furthermore, based on the concept of Imam Shatibi's higher objective (Raysuni, 2005), the indicators for Islamic-based hotels can be divided into 6 goals, and a total of 44 indicators. A further finding is that qualitative research (58%) is still more prevalent than the quantitative approach (42%).